2022
DOI: 10.1007/s42773-022-00171-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of MgO hybrid biochar and its mechanism for high efficient recovery of phosphorus from aqueous media

Abstract: Conversion of organic waste into engineered metal-biochar composite is an effective way of enhancing biochar’s efficiency for adsorptive capture of phosphorus (P) from aqueous media. Thus, various strategies have been created for the production of metal-biochar composites; however, the complex preparation steps, high-cost metal salt reagent application, or extreme process equipment requirements involved in those strategies limited the large-scale production of metal-biochar composites. In this study, a novel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Previous studies showed that the MgO functionalized biochar can adsorb P; however, the P-loaded MgO-biochar showed low desorption abilities when using distilled water, NaCl, NaNO 3 , Na 2 CO 3 , and NaOH solutions, while it showed a higher desorption abilities with acidic solutions such as HCl or HAc (Yao et al 2011;Li et al 2016;Xu et al 2018;Zhu et al 2020Zhu et al , 2021Fang et al 2022). Therefore, 0.01 mol L −1 HAc solution was selected as the desorption reagent in this study.…”
Section: Recycling Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies showed that the MgO functionalized biochar can adsorb P; however, the P-loaded MgO-biochar showed low desorption abilities when using distilled water, NaCl, NaNO 3 , Na 2 CO 3 , and NaOH solutions, while it showed a higher desorption abilities with acidic solutions such as HCl or HAc (Yao et al 2011;Li et al 2016;Xu et al 2018;Zhu et al 2020Zhu et al , 2021Fang et al 2022). Therefore, 0.01 mol L −1 HAc solution was selected as the desorption reagent in this study.…”
Section: Recycling Studiesmentioning
confidence: 94%
“…Traditional adsorbents, including zeolite, ion exchange resin, and diatomaceous earth face several challenges, including high cost, low P sorption capacity, and difficulty in reuse (Jiang et al 2013;Xia et al 2016). Thus, developing low-cost adsorbents with high efficiency continuously attracts researchers' attention (Fang et al 2022;Wu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, biochar (BC) is a highly aromatic porous solid material with strong adsorption ability produced by pyrolysis of biomass waste at relatively low temperatures (<700 °C) [ 14 , 15 ]. In recent years, the application of biochar has become an emerging technology in environmental use.…”
Section: Introductionmentioning
confidence: 99%
“…As an auxiliary composting material, biochar has been used as an amendment to improve the compost quality and to shorten the maturity process during the composting process since recently [ 16 , 17 ], and the above-mentioned effects of BC for storing moisture and nutrients also mean that the biomass waste is better degraded microbiologically. Many reports have proved that BC could be used as amendments to the nitrogen assimilation ability of microorganisms and to reduce nitrogen loss in composting [ [18] , [19] , [20] , [21] ], to enhance microbial activity [ 14 , 16 , 22 ] and to facilitate the composting process, to decrease the water-soluble carbon content and to reduce the mobility of heavy metals [ 17 , 18 , 23 ]. Besides, researchers proposed a sustainable biochar concept, through which the emission of greenhouse gases including nitrous oxide (N 2 O) and methane (CH 4 ) can be avoided [ [24] , [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%
“…The excessive generation of this organic waste has resulted in serious socioeconomic and environmental problems worldwide, such as resource waste, environmental contamination, global climate change, and ecosystem degradation (Afolalu et al 2022;Misslin et al 2022). Looking for green and alternative approaches is an important way towards organic waste management and utilization, which will power our future with low-or zero-carbon emissions and strong sustainability (Liu et al 2012;Fang et al 2022). The resource utilization and harmless treatment of organic waste is an effective way to control environmental pollution, improve environmental quality, develop a circular economy, and achieve sustainable development (Kharola et al 2022;Peng et al 2022).…”
mentioning
confidence: 99%